Economic Recovery Strategy Through Tourism Amid the COVID-19 Pandemic - Inrinofita Sari; Rosmita; Nuryanti Mustari (Universitas Muhammadiyah Malang, 2022)
This study looks at the economic recovery strategy through tourism amid the Covid-19 pandemic. This study uses qualitative research, which uses literature or literature review to obtain data. This research sends information on research maps using export data to RIS Export file format, which is then processed using VOSviewers to determine big data to be analyzed to obtain comparative data results. This research with previous research. In the second Discussion, the author processes data using Nvivo 12 to explore and describe economic recovery strategy through tourism amid the Covid-19 pandemic to explain data efficiently. The findings in this study are that foreign tourist visits to Indonesia based on data from the Ministry of Tourism and Creative Economy decreased compared to August 2019, in 2020, amounting to 4,052,923 visits or reduced by 74.84% compared to 2019, which amounted to 16,108,600. The economic recovery strategy was developed to accelerate tourism recovery, namely by providing assistance to tourism business actors in adapting new habits, encouraging tourism business productivity and tourism workers with digital adaptation, providing fiscal and non-fiscal stimulus to tourism businesses and workers, developing the domestic tourist market and build market confidence in the tourism sector.